Herbal Medicines as Cancer Treatment: A Narrative Literature Review - Awan Rochaniawan (Open Access Indonesian Journal of Medical Reviews, 2021)
Cancer is a devastating disease that affects millions of people around the world. Despite significant advances in cancer treatment over the years, including chemotherapy, radiation therapy, and surgery, many patients still experience significant side effects and poor outcomes. As a result, there has been growing interest in alternative and complementary therapies, including herbal medicine. Herbal medicine, also known as botanical medicine, is the use of plants and plant extracts for medicinal purposes. This practice has been used for thousands of years and is still commonly used in many cultures around the world. In recent years, there has been growing interest in the use of herbal medicine as a cancer treatment. Many herbs and plant extracts have been found to contain compounds that have anti-cancer properties. These compounds can help to kill cancer cells, prevent the growth and spread of tumors, and reduce the side effects of cancer treatment.